Karakteristik Individu dan Stres Kerja pada Operator Unit Produksi di Industri bidang Ketenagalistrikan: Analisis Usia, Masa Kerja, dan Tingkat Pendidikan - Sevina Nabilah Khansa; Putri Ayuni Alayyannur (Lembaga Pengembangan Kinerja Dosen, 2026)
Work stress is an occupational health issue that can affect workers’ well-being and job performance. Individual responses to work stress may vary and can be affected by individual characteristics such as age, length of service, and educational level. The relationship between individual characteristics and workstress among operators at PT X was examined in this study. This study used a quantitative descriptive correlational design with a cross-sectional approach. The study was involving 31 operators from the production unit of PT X selected using random sampling. Work stress data were collected using the OSI-R™ questionnaire and analyzed using the Spearman correlation test. Most respondents were aged 45–54 years (42%), had ≥30 years of service (58%), and had a senior high school/vocational education level (61%). Most operators experienced moderate work stress (55%). The analysis age and length of service were significantly related to work stress (p < 0.001), while educational level was not significantly related to work stress (p = 0.518). Age and length of service were associated with work stress among PT X operators, where older workers and those with longer tenure tended to experience lower work stress.